2016
DOI: 10.1042/bcj20160523
|View full text |Cite
|
Sign up to set email alerts
|

The zebrafish homologs of SET/I2PP2A oncoprotein: expression patterns and insights into their physiological roles during development

Abstract: The oncoprotein SET/I2PP2A (protein phosphatase 2A inhibitor 2) participates in various cellular mechanisms such as transcription, cell cycle regulation and cell migration. SET is also an inhibitor of the serine/threonine phosphatase PP2A, which is involved in the regulation of cell homeostasis. In zebrafish, there are two paralogous set genes that encode Seta (269 amino acids) and Setb (275 amino acids) proteins which share 94% identity. We show here that seta and setb are similarly expressed in the eye, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 63 publications
1
12
0
Order By: Relevance
“…1 B). Similar results were obtained upon targeting both seta and setb genes in the transgenic embryos with a translation blocking morpholino (MOab) 36 (Fig. 1 S).…”
Section: Resultssupporting
confidence: 78%
See 2 more Smart Citations
“…1 B). Similar results were obtained upon targeting both seta and setb genes in the transgenic embryos with a translation blocking morpholino (MOab) 36 (Fig. 1 S).…”
Section: Resultssupporting
confidence: 78%
“…Previous work of our lab has shown that the zebrafish homologs of SET oncoprotein are expressed during early zebrafish development and localized in the ciliated organs of zebrafish, suggesting a potential function of SET in signaling cascades coordinated by cilia 36 . This study also demonstrated that targeting setb gene expression by injections of setb gRNA with Cas9 mRNA or seta/b morpholinos into one-cell stage zebrafish embryos resulted in several morphological abnormalities, including defects in spinal cord and eye development 36 . A systematic scoring of the eye defects in setb crispants showed that approximately 80% of the larvae with severe phenotype and 33% of the larvae with moderate phenotype exhibited cyclopia (Fig.…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…After fixation, larvae were washed twice with PBS, transferred to 100% methanol, and stored at −20 °C. Acetylated tubulin staining was performed as previously described [58].…”
Section: Methodsmentioning
confidence: 99%
“…54,55 For example, Serifi et al 56 combined CRISPR and morpholino techniques and found that the Setb gene in zebrafish, a paralog of the human SET/I2PP2A gene, has a role in the development of the retina. 56 Another example of using SpCas9-generated knockouts and morpholinos together was shown by Taylor et al, 57 who targeted a notch-signaling pathway protein, NeuroD, to show its important role in photoceptor regeneration.…”
Section: Crispr-cas Genome Surgery In Animal Models Of the Eyementioning
confidence: 99%